2014
DOI: 10.1111/wvn.12036
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Support Protocols and Their Influence on the Delivery of Enteral Nutrition: A Systematic Review

Abstract: The use of a nutrition support protocol appears to increase the efficacy of enteral nutrition delivery. Further research is needed to determine the effect of increased enteral nutrition adequacy on patient outcomes. The use of an evidenced-based protocol is recommended to improve protein and energy delivery in the critically ill.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…The use of evidence‐based feeding protocols for the commencement and escalation of enteral nutrition have been well researched in the critical care setting, whereas the use of a protocol to guide the transition from EN to ON in the acute setting is novel. Findings of this study demonstrated similar improvements in consistency of nutrition delivery to previous studies in the critical care setting . Prior to implementation of the TFP, feeding practices were observed to be inconsistent with various forms of TF being administered, and a high proportion of patients ceasing EN without dietetic intervention.…”
Section: Discussionsupporting
confidence: 72%
“…The use of evidence‐based feeding protocols for the commencement and escalation of enteral nutrition have been well researched in the critical care setting, whereas the use of a protocol to guide the transition from EN to ON in the acute setting is novel. Findings of this study demonstrated similar improvements in consistency of nutrition delivery to previous studies in the critical care setting . Prior to implementation of the TFP, feeding practices were observed to be inconsistent with various forms of TF being administered, and a high proportion of patients ceasing EN without dietetic intervention.…”
Section: Discussionsupporting
confidence: 72%
“…Regardless of strategy, ICU EN feeding protocols help to promote compliance with clinical practice guidelines–directed nutrition practices and lead to optimization of nutrition therapy as a whole 28 , 29 . A review of 19 studies demonstrated that protocol implementation has a positive impact on the number of patients receiving nutrition therapy, the optimization of volume intake, the time to initiation of nutrition therapy, and the number of days with nutrition therapy and yields better reported outcomes related to feeding optimization 30 …”
Section: Discussionmentioning
confidence: 99%
“…Combating this double burden of malnutrition (DBM) has become a significant global health challenge in many healthcare settings [36]. DBM is characterized by the coexistence of undernutrition along with obesity or diet-related noncommunicable disease and is associated with poor outcomes and increased cost of hospitalization [20, 36]. Literature has shown that nutritional therapy, both enteral and parenteral, is the most cost-effective intervention in managing malnutrition in critical illness before ICU admission and after discharge, including the rehabilitation period [37–39].…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the highlighted benefits, a number of barriers to effective implementation of nutritional therapy guidelines exist [18]. In many clinical settings, decisions made by healthcare providers involved in the nutrition care of critically ill patients are found not to be based on scientific evidence, leading to varied nutritional practices in many ICUs, even within a single hospital [19, 20].…”
Section: Introductionmentioning
confidence: 99%